Land use/cover change, and future scenarios in the coastal region of Oaxaca state, Mexico - Leija-Loredo, Edgar G.; Reyes-Hernández, Humberto; Reyes-Pérez, Oscar; Flores-Flores, José L.; Sahagún-Sanchéz, Francisco J. (Instituto de Ecología, A.C., 2016)
Oaxaca state is considered one of the most important Mexican hot spots because of the huge richness and diversity it contains, and the increasing conversion of forests and tropical forest that threatens the integrity and stability of these tropical ecosystems. The objectives of this study were to analyze changes in land cover and land use in two municipalities of the coastal region of Oaxaca State for 2000-2011, to understand their causes and to model future scenarios of such transformations to 2025. The study was based in the spatial-temporal mapping of vegetation and land use, derived from satellite images Spot and Landsat ETM+. Once trends of changes in land cover (2000-2011) were established, scenarios to 2025 established by a spatially explicit model. The results indicate that 18 403 ha were deforested in the rain forests in eleven years, 369 ha of temperate forests and 421 ha of mangroves. If this trend continues in 2025, 37 937 ha of rain forests 650 ha and 885 ha of mangrove forests will be lost. Given this scenario it is essential to define strategies for the conservation of ecosystems and to simultaneously improve the living conditions of the inhabitants of this region.